PELATIHAN PENGUATAN LITERASI KIMIA BAGI LABORAN DAN PENGELOLA LABORATORIUM IPA - Subamia, I Dewa Putu; Wahyuni, I.G.A.N. Sri; Widiasih, Ni Nyoman (Universitas Pendidikan Ganesha, 2019)
Community service activities (P2M) have been implemented in the form of training in strengthening chemical literacy for laboratory assistants and managers of junior high science laboratories in Buleleng Regency. This activity aims to provide strengthening and enhancement of the ability of chemical literacy of Labors and Managers of Science Laboratory. The method used is the education-training and mentoring method. Implementation form is in service and on service in the form of lectures, workshops practices. Realization of activities includes the identification of potentially hazardous materials, substance of science practicum, characterizing the risk of hazardous chemicals, identifying ways to handle and mitigating chemical hazards, maintaining safety and health work in the laboratory and how to handle accidents due to chemicals. The outputs of this activity are posters/work instructions for hazardous chemicals in the science laboratory, chemistry literacy modules, increased competence in chemical literacy, and the scientific article in a national journal.